2020
DOI: 10.3892/or.2020.7592
|View full text |Cite
|
Sign up to set email alerts
|

An elongated tract of polyQ in the carboxyl‑terminus of human α1A calcium channel induces cell apoptosis by nuclear translocation

Abstract: An aberrant elongated tract of glutamine residues (polyQ) in proteins induces multiple diseases treated in the clinic. In our previous study of progressive myoclonic epilepsy (PME), using whole-exome sequencing, a mutant Cav2.1 protein with an aberrant elongated polyQ tract was identified in PME patients. To investigate the molecular mechanism and cell biology of this aberrant elongated polyQ tract, wild-type Cav2.1 with 13 polyQ repeats (Cav2.1 wt-Q13) and mutant-type Cav2.1 with 26 polyQ repeats (Cav2.1 mt-Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…HEK-293 and PC12 cells for spinocerebellar ataxia type 6 [ 191 ]. SH‑SY5Y cells for progressive myoclonic epilepsy [ 161 ] AAV9-mediated delivery of miR-3191-5p in mice rescued ataxia, motor deficits, and purkinje cell degeneration [ 165 ] MiRNA-3191-5p prevented the hyperacute disease in hyperacute model of spinocerebellar ataxia type 6 mice [ 226 ] SIS-RNAi could rescue spinocerebellar ataxia type 6 [ 160 ] Barbiturate pentobarbital could block Cav2.1 current [ 166 ] Acetazolamide had no effect on HEK cells carrying mutation for episodic ataxia type 2 [ 145 ] Apoptotic pathway in progressive myoclonic epilepsy [ 161 ] Apoptotic pathway in ataxia [ 191 ] CACNA1C Calcium voltage-gated channel subunit alpha1 C Cav1.2 L-type None Human induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) for long-QT syndrome phenotype [ 162 ]. Induced pluripotent stem cell (iPSC) knockout resource for autism spectrum disorder [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HEK-293 and PC12 cells for spinocerebellar ataxia type 6 [ 191 ]. SH‑SY5Y cells for progressive myoclonic epilepsy [ 161 ] AAV9-mediated delivery of miR-3191-5p in mice rescued ataxia, motor deficits, and purkinje cell degeneration [ 165 ] MiRNA-3191-5p prevented the hyperacute disease in hyperacute model of spinocerebellar ataxia type 6 mice [ 226 ] SIS-RNAi could rescue spinocerebellar ataxia type 6 [ 160 ] Barbiturate pentobarbital could block Cav2.1 current [ 166 ] Acetazolamide had no effect on HEK cells carrying mutation for episodic ataxia type 2 [ 145 ] Apoptotic pathway in progressive myoclonic epilepsy [ 161 ] Apoptotic pathway in ataxia [ 191 ] CACNA1C Calcium voltage-gated channel subunit alpha1 C Cav1.2 L-type None Human induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) for long-QT syndrome phenotype [ 162 ]. Induced pluripotent stem cell (iPSC) knockout resource for autism spectrum disorder [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic pathway in progressive myoclonic epilepsy [ 161 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional analysis in the cell line model (SH-SY5Y neuroblastoma cell line) revealed that CAG repeats of pathogenic expansion in the C-terminus of the CACNA1A gene probably lead to activation of apoptosis factors (Bcl-2/Bax, caspase, and PARP) and induce cell apoptosis in nerve cells. This finding can provide new insights for the treatment of Progressive Myoclonic Epilepsy (PME) [ 21 ]. Ataxia, myoclonus seizures, and progressive cognitive impairment are some features that are usually present in PME patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%